PENERAPAN HUKUM PADA TINDAK PIDANA PENCABULAN SESAMA JENIS TERHADAP ANAK DI INDONESIA - Kurniawan, Edi; Panjaitan, Saut Parulian; Yuningsih, Henny (Solusi, 2024)
Cases of obscenity are currently rife in indonesia. the victims in these crimes are often childrenthe causative factor is that this act of same-sex abuse begins with a sexual deviance experienced by an individual who likes same-sex sexual or in other words is driven by homosexual behavior. (for fellow women to be called lesbians) is emotional attraction (affection, emotional connection) and/or erotically, either more prominently (predominantly) or solely (exclusively), towards people of the same sex. the same, with or without physical (physical) intercourse. the regulation or legal basis governing obscene acts is regulated in chapter xiv of the criminal code (kuhp) concerning crimes against decency, namely in articles 289 to article 296 of the criminal code. article 289 of the criminal code contains obscene acts with violence or threats of violence, while articles 290 paragraphs (2) and (3), 292, 293, and 294 paragraph (1) of the criminal code contain the crime of obscenity with the criminal code contains the criminal act of obscenity with child victims.